2016
DOI: 10.1177/1420326x15606507
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of radiation hazards due to exposure to radionuclides in marble and ceramic commonly used as decorative building materials in Egypt

Abstract: The concentrations of 238 U (226 Ra), 232 Th, and 40 K for the commonly used decorative building materials (15 marble and 15 ceramic) in Egypt were measured using gamma spectroscopy system. Radionuclides concentrations in marble samples were ranged from:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…marble and ceramic were below the world average value, where the potassium was higher than the standard limit. 70 The activity level of thorium was found to be higher than radium, which may be due to the abundance of thorium being greater than radium in the soil of Malaysia which is presented in Table 1.…”
Section: Resultsmentioning
confidence: 95%
“…marble and ceramic were below the world average value, where the potassium was higher than the standard limit. 70 The activity level of thorium was found to be higher than radium, which may be due to the abundance of thorium being greater than radium in the soil of Malaysia which is presented in Table 1.…”
Section: Resultsmentioning
confidence: 95%
“…The prepared samples were packed into airtight plastic cylindrical containers (6 cm diameter and 4 cm height) made from polyethylene. The containers were carefully sealed with an adhesive to prevent any possibility of radon ( 222 Rn) or thoron ( 220 Rn) escaping and stored for one month to achieve radioactive secular equilibrium between radium and radon 14 . At the same time, an empty container, with the same geometry as used for the samples, was also sealed and left for the same time in order to be used for background measurement.…”
Section: Experimental Techniquementioning
confidence: 99%
“…The potassium ( 40 K) specific activity concentration was estimated from the γ-ray’s energy of 1460.9 keV (10.67%) associated with the decay of 40 K. The specific activity concentration of these natural radionuclides, A , (Bq kg −1 ) was calculated from Eq. (1) 14,18 .where C is the net count above the background, p is the absolute emission probability of the gamma ray (mentioned in brackets after γ-rays energies), w is the net dry sample weight (kg), t is the measurement time which was adjusted for all measurements to be 80000 seconds, and ε is the absolute efficiency of the detector.…”
Section: Experimental Techniquementioning
confidence: 99%
“…The soil (upper layer of the earth's crust) is one of the most important sources of naturally occurring radioactive materials (NORM), i.e. uranium series, thorium series and potassium [1][2][3][4]. UNSCEAR, 2000 [5] reported that the main contributor of human beings' exposure comes from natural radiation, and the worldwide average annual effective dose is 2.4 mSv.…”
Section: Introductionmentioning
confidence: 99%